Technological and organizational changes, and labor flows: evidence on French establishments - Philippe Askenazy; Eva Moreno-Galbis (Institute for the Study of Labor (IZA), 2007)
This paper investigates the effects of organizational and technological changes on job stability of different occupational categories in France. We conduct an empirical analysis in which we make extensive use of a unique data set on a representative sample of French establishments. Working with various indicators of labor flows (gross labor flows, hiring rate, firing rate, net labor flows and churning flows), we find that the use of new technology seems to have a positive effect on aggregate job turnover and, more specifically, turnover among manual workers. In contrast, innovative workplace organizational practices are related to lower turnover among clerical workers and intermediate professionals and have a positive effect on churning among managers
urn:nbn:de:101:1-20080425475
Keywords: 330; Arbeitsplatzsicherung; Arbeitsmobilität; Computergestütztes Verfahren; Technischer Fortschritt; Arbeitsorganisation; Organisatorischer Wandel; Schätzung; Frankreich